EFEKTIVITAS PEMBERIAN MINUMAN KUNYIT ASAM TERHADAP PENURUNAN NYERI HAID ATAU DISMENORE PADA REMAJA PUTRI DI ASRAMA STIKES DUTA GAMA KLATEN - Dessy Novitasari; Siti Yulaikha; Feri Catur Yuliani (STIKES DUTAGAMA KLATEN, 2015)
Background: The adolescent is a transfer period from child to adult, in this period the change happened, the physiological or psychological. One of physiological change is the change of reproduction, it can be see from the menstruation. Half of the woman suffer from the menstruation, almost of them suffer in the bottom of the stomach before or during menstruation. The turmeric drink is one of the drinks made of turmeric and tamarind, the turmeric is believed as an analgetic, anti pyretics and anti inflammatory (Limananti dan Triratnawati, 2003). Goal: the goal of the research is to know the effectiveness of drinking tamarind turmeric to reduce the menstruation painful (dismenorea) to the adolescent girls in Stikes Duta Gama Dormitory Klaten in 2015. Research Methodology: The research use pra experiment One Group Pretest Posttest. The samples are 33 respondences with purposive sampling technique. The level of painful was measured used NRS. The data analysis is parametric statistic Paired t-test. Result: the result of the research showed that drank of nurmeric was effective to reduce the menstruation painful to the adolescent girls in Stikes Duta Gama Dormitory Klaten with the result ρ = 0,000 ( ρ < 0,05 ). Conclusion: Drank tamarind turmeric effective to reduce the menstruation painful during the menstruation. Tamarind turmeric drink had benefits as an analgetic and anti-inflammatory. The content of the turmeric and tamarind can reduce the lamentation of dismenorea.